Cream of leaf pare extract (momordica caharantia l) 4% takes the improvement of effective melanin numbers with 4% hydrocuinon cream on marmut skin (cavia porcellus) heart which uses uvb ultraviolet light - Mery Merysia; Wimpie Pangkahila (Fakultas Kedokteran Universitas Udayana, 2018)
Introduction: Bitter melon leaves is one of the plants that can be used as an antioxidant and antimelanogenic. The active compounds in bitter melon leaves are flavonoids, phenolic acids, tannins and vitamin C. The purpose of this study was to determine the effectiveness of 4% pare (Momordica charantia) leaf extract cream with 4% hydroquinone cream in inhibiting the increase of melanin in marmot skin (Cavia porcellus) which was exposed to ultraviolet light B. Method: This study used experimental study with a randomized post-test only control group design method. This study used 36 male guinea pigs (Cavia porcellus), local strains, 3 months of age with a body weight of 300-350mg, divided into 2 groups, with 18 individuals each. The first group was received 4% hydroquinone cream and exposed to ultraviolet B while the second group received 4% bitter melon extract (Momordica charantia) and also exposed to ultraviolet light B 3x a week with a total irradiation dose of 390 mJ/cm2 for 2 weeks. Results: The results showed that the control group (P0) had a mean number of melanin 0.98 ± 0.25% pixel and the treatment group (P1) had an average number of melanin 1.17 ± 0.34% pixels. The difference was analyzed by t-independent test and found to be insignificant (p = 0.06). Statistical analysis found no significant differences in the number of melanin between the control group and the treatment group (p = 0.06). Conclusion: The results showed that the 4% ethanol extract of pare leaves (Momordica charantia) was as effective as hydroquinone cream in inhibiting the increase in the amount of melanin in the skin of male guinea pigs (Cavia porcellus) exposed to UVB rays.